The impact of green investments on Philippine energy firms’ financial performance: The moderating role of environmental policies - Al-ag, Byrne Joshua B. (Animo Repository, 2023)
This research examined the profitability of select 9 renewable and non-renewable energy firms from the Philippines. This study investigated the impact of green investments on return on equity, Q ratio, and net profits. A dynamic panel data regression containing 53 observations from 2016 to 2021 was conducted. A Granger causality test was also conducted to determine the causality of green investments to the variables. The regression results indicated that green investment has no significant association with net profits but has a positive association with return on equities. It was also found that Q ratio has a negative association with green investments while causality was found lacking through Granger's test. This study will help companies in making informed decisions in investing through the analytical evaluation of the results. It can also provide valuable insights for the government in promoting or advocating green investments.